PROSES BELAJAR MELALUI KERJA SAMA: TUGAS DISKUSI DAN RESITASI DALAM PEMBELAJARAN KELAS RANGKAP DI SD NEGERI KALIPUCANG - Albita Intan Viola; Zela Septikasari (STKIP Subang, 2026)
This study's objective is to explain how task-based, discussion-based and repetition-based teaching approaches are used in multigrade classes at Kalipucang State Primary School. This investigation used a descriptive qualitative methodology, with information gathered from documentation, interviews, and observation. The headteacher, teachers and pupils served as informants in this study. The phases of data analysis included data reduction, data display, and conclusion-making. The results show that the task-based approach keeps pupils engaged in independent learning activities whilst the teacher guides other groups. Pupils are encouraged to engage, collaborate and participate actively in learning tasks through discussion techniques. Meanwhile, the recitation method provides pupils with the opportunity to present their learning outcomes whilst also serving as a means of assessing their understanding of the material. The application of these three methods supports the creation of active, collaborative and pupil-centred learning in the implementation of multi-grade classroom teaching.